Human Cortical Activity Evoked by the Assignment of Authenticity when Viewing Works of Art - Huang, Mengfei; Bridge, Holly; Kemp, Martin J.; Parker, Andrew J. (Frontiers in Human Neuroscience, 2011)
The expertise of others is a major social influence on our everyday decisions and actions. Many viewers of art, whether expert or naïve, are convinced that the full esthetic appreciation of an artwork depends upon the assurance that the work is genuine rather than fake. Rembrandt portraits provide an interesting image set for testing this idea, as there is a large number of them and recent scholarship has determined that quite a few fakes and copies exist. Use of this image set allowed us to separate the brain’s response to images of genuine and fake pictures from the brain’s response to external advice about the authenticity of the paintings. Using functional magnetic resonance imaging, viewing of artworks assigned as “copy,” rather than “authentic,” evoked stronger responses in frontopolar cortex (FPC), and right precuneus, regardless of whether the portrait was actually genuine. Advice about authenticity had no direct effect on the cortical visual areas responsive to the paintings, but there was a significant psycho-physiological interaction between the FPC and the lateral occipital area, which suggests that these visual areas may be modulated by FPC. We propose that the activation of brain networks rather than a single cortical area in this paradigm supports the art scholars’ view that esthetic judgments are multi-faceted and multi-dimensional in nature.